Architect and professor Yu. F. Dmitrievsky (1924–1991) - Druzhinina, Inna (project baikal, 2023)
Over time, the recognition of authors of even famous objects is lost in professional circles. With this oblivion, history is gradually lost too. This article aims at restoring the memory of a famous Irkutsk professor, who was less famous as an architect though. The article applies the method of empirical research and the method of exclusion. The research is based on the archival materials of the Irkutsk Regional Organization of the Union of Architects of Russia. A preliminary study of archival materials was carried out to photograph the objects. Some biographical facts and pages of Yu. F. Dmitrievsky’s creative life were reconstructed.